The management and valuation of quarries / Radiah Mustaffa - Mustaffa, Radiah (1987)
The term "quarry" can be defined as an open or surface working, usually for the extraction of building stone, as slate, limestone etc. In its widest sense, the term mine includes quarries, and has been sometimes so construed by the courts; but when the distinction is drawn, mine denotes underground workings and quarry denotes superficial workings. Products (other than petroleum) exploitable from below the earth's surface are divided into two categories, namely "metals and minerals" on the one hand and "rock materials" on the other. The Mining Enactment (Cap. 147) defines "mining" or "to mine" as, " to distinguish, remove, cart, carry, wash, sift, smelt, refine, wash or otherwise deal with any rock, stone, gravel, clay, sand, soil or mineral by any mode or method whatever for the purpose of obtaining metal or mineral there from "